Evaluation of livestock identification and traceability system - Gou, Xue Ni (2016)
Livestock identification was probably first introduced when animal husbandry was developed, as a means of proving ownership. Accompanied the development of identification, the concept of animal traceability emerged which refers to the ability to follow an animal or group of animals during all stages of its life. Livestock Identification and Traceability (I&T) system developed worldwide in practice with more formal procedures and more complex systems. The selection of appropriate livestock I&T system is a complicated issue where no clear-cut rule is available. Therefore, evaluation of livestock I&T systems is carried out in this research to assist decision makers in the optimal decisions. In this research, a group of qualitative characteristics of livestock I&T system was captured via knowledge mining process and expert consultations. Qualitative evaluation was then carried out within a multi-criteria qualitative evaluation framework. Case studies were conducted to investigate the development of livestock I&T system in selected countries/regions. Besides the unique variables acquired by means of case studies, the multi-criteria evaluation framework supports a more systemised and comparable analysis in different contexts. Quantitative evaluation of livestock I&T system was then conducted on the contagious disease control based on the adapted state-transition simulation model. Base case simulation results with the default values have shown the superiority of more advanced systems in help controlling contagious diseases. More importantly, the simulation results have revealed several conditions in which advancement of I&T system plays a more vital role. When the initial disease attack is more severe, the selection of livestock I&T system will more significantly influence the disease control results. Similarly, when the livestock population is less immunisation prepared, being it either poor general immunity status or poor responsiveness in emergency immunity, I&T systems will have a more profound impact on disease control. If the specific regional conditions are more favorable for traceability systems, better outcome of disease control is expected. Among different livestock I&T systems, the more advanced system depends less on the regional conditions to deliver satisfied performance. This evaluation model based on the adapted state-transition simulation can be a useful tool in making optimal decisions regarding the choice of livestock I&T system. It provides general guidelines in the selection process, particularly for countries/regions with insufficient dataset for a more complete and complicated livestock disease model. The livestock I&T system was further analysed for its impact on the development of dedicated livestock disease insurance. While livestock disease insurance is a desirable and promising way to fund potential catastrophic losses, its progress is stagnant due to a few development obstacles. Livestock I&T system plays a potential role to support its positive development. In this study, the impact of livestock I&T system on the catastrophic loading of insurance was examined through simulation using the catastrophe risk model. The performance of different livestock I&T systems in this aspect was evaluated with the event sets generated from the sample scenario in the North American Animal Disease Spread Model (NAADSM). The catastrophe risk analysis revealed the important contribution of improving I&T system in relieving catastrophe risk loading on the insurance providers. Meanwhile, if the most advanced system with very prompt tracing and pre-emptive destruction was adopted, dedicated livestock disease covers need to be supplemented with public funds for more sustainable development.